2020
DOI: 10.1111/csp2.293
|View full text |Cite
|
Sign up to set email alerts
|

Examining the public's awareness of bee (Hymenoptera: Apoidae: Anthophila) conservation in Canada

Abstract: Understanding the general public's knowledge and perceptions of an issue can help drive action on the part of decision-makers. Such understanding is critical when decision-makers are faced with multiple stakeholders, which is the case with biodiversity conservation issues. We surveyed the Canadian general public using a telephone questionnaire to assess the level of knowledge and perceptions of native wild bee (Hymenoptera: Apoidea: Anthophila) health and conservation. We found that the general level of bee kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Semantic network analyses revealed that student understanding of bees is dominated by concepts that are either specific to or closely associated with honey bees and that connect mainly to bees' basic functions and utilitarian value for humans. This is consistent with results from van Vierssen Trip et al (2020), who found in a recent survey of the Canadian public that half of participants listed honey bees ( Apis mellifera ) as a native bee of Canada—though this bee was imported to North America from Europe in the 1600s (Carpenter & Harpur, 2021)—and a majority of respondents listed honey and pollination as the most important reason to conserve bees. Moreover, coding of student statements about bees revealed that their understanding tended to be fairly accurate, but not very sophisticated.…”
Section: Discussionsupporting
confidence: 89%
“…Semantic network analyses revealed that student understanding of bees is dominated by concepts that are either specific to or closely associated with honey bees and that connect mainly to bees' basic functions and utilitarian value for humans. This is consistent with results from van Vierssen Trip et al (2020), who found in a recent survey of the Canadian public that half of participants listed honey bees ( Apis mellifera ) as a native bee of Canada—though this bee was imported to North America from Europe in the 1600s (Carpenter & Harpur, 2021)—and a majority of respondents listed honey and pollination as the most important reason to conserve bees. Moreover, coding of student statements about bees revealed that their understanding tended to be fairly accurate, but not very sophisticated.…”
Section: Discussionsupporting
confidence: 89%
“…To test whether people value gardening more if they faced more personal hardships during the COVID-19 pandemic (Q3), we used ordinal logistic regression models fit with a probit link function using clm in ordinal ( Christensen, 2019 ) to test for relationships between the number of COVID-related daily difficulties and number of concerns about accessing food with: (i) each of the eleven components on the importance of gardening, and (ii) each of the five components on changes in gardening activity. For this analysis, we reclassified the response variables due to skewed distribution across the dataset following others ( Vierssen Trip et al, 2020 ). For the importance of gardening responses, we reclassified the 5-Point Likert scale responses into three ordinal responses: “not important” (1 on scale; “not at all important”), “somewhat important” (combined 2, 3 and 4 on scale; “slightly important”, “moderately important” and “very important”), and “very important” (5 on scale; “extremely important”).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing public attention on the existence and importance of wild urban bees provides a great opportunity for biodiversity conservation in cities. However, the Western honey bee ( Apis mellifera L.) is oddly perceived as a symbol of biodiversity conservation by many citizens, the mass media, and institutions across the globe ( Smith & Saunders, 2016 ; Van Vierssen Trip et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%